Violent video games and aggressive behaviour with parental monitoring as moderator among adolescents in Petaling, Selangor, Malaysia - Ahmad Zaki, Azimah (2017)
There is growing interest in linking media violence with aggressive behaviour in adolescence. Some argue that with sufficient parental monitoring, such influence will reduce. Though studies have been conducted in the west, fewer found in the eastern contexts such as Malaysia. Other factors influencing aggressive behaviour include sex, age, family income, and religiosity. Thus, this study aims to determine the relationship between exposure to violent video games and personal background in relation to aggressive behaviour; examine the moderating effects of parental monitoring; and determine the factors that uniquely predict aggressive behaviour. For this quantitative study, respondents were selected using multiple-stage sampling. There were 206 respondents age 13 to 14 years old. Self-administering questionnaire was used to collect data using four valid and reliable instruments which includes the General Media Habits Questionnaire - Child Version (Gentile, Lynch, Linder, & Walsh, 2004), Daily Spiritual Experience Scale (Underwood, 2006), Adult Involvement in Media Scale – Child Version (Gentile, Nathanson, Rasmussen, Reimer, & Walsh, 2012), and Buss-Perry Aggression Scale (Buss & Perry, 1992). The result on variables score shows that respondents score high in religiosity while low in aggressive behaviour. While scores for violent video games exposure and parental monitoring are nearly equal distribution of high and low scores. The correlation analysis demonstrates significant correlation between sex, family income, and violent video games exposure with aggressive behaviour, though correlations are low. Hierarchical multiple regression analysis presents that parental monitoring significantly moderate the interaction between violent video games exposure and aggressive behaviour. Interaction between violent video games exposure and aggressive behaviour is strongest for high parental monitoring. The findings of the study suggest that violent video games exposure, sex, and family income are related to aggressive behaviour. The results also suggest that high parental monitoring can reduce the effects of violent video games exposure on aggressive behaviour. The results provide implication for parents, policy makers, non-profit organisations, and society of possible effects of exposure to violent video games, sex, and family income on aggressive behaviour, and develop prevention and intervention programmes against aggressive behaviour among adolescents.